Good Governance as a Strategy to Improve the Quality of Public Services in Gowa Regency Public Service Mall - Fitri Handayani; Muhlis Madani; Nurbiah Tahir (Universitas Muhammadiyah Makassar, 2026)
Abstract : Public service is an important indicator in realizing good governance. In the era of bureaucratic reform and digital transformation, the public demands transparent, accountable, effective, efficient, responsive, and equitable services. One of the government's innovations in improving the quality of public services is the establishment of the Public Service Mall (MPP). This study aims to analyze the application of good governance principles as a strategy to improve the quality of public services at the Gowa Regency Public Service Mall and identify supporting and inhibiting factors. This study uses a qualitative method with a descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation. Data were analyzed through data reduction, data presentation, and drawing conclusions. The results show that the implementation of good governance at the Gowa Regency Public Service Mall has been running quite well through the application of the principles of transparency, accountability, effectiveness and efficiency, responsibility, and equality. The improvement in the quality of public services is evident in the public service compliance score of the Republic of Indonesia Ombudsman which increased from 79.69 in 2022 to 94.37 in 2024 with the highest quality green zone category. Supporting factors include local government commitment, adequate service facilities, and the use of digital technology. Meanwhile, inhibiting factors include limited human resources, low digital literacy, and internet network disruptions. This study concludes that the implementation of good governance has positively contributed to improving the quality of public services at the Gowa Regency Public Service Mall. Keywords: good governance; public service; public service mall; service quality; bureaucratic reform